Crescimento e desempenho de bertalha (basella alba l.) em função do tipo de propagação - Da Silva Campos, Renê Arnoux; Lima, Giuseppina Pace Pereira [UNESP]; William, Santino Seabra; Takata, Hiroshi Suekane [UNESP]; Da Silva, Ewerton Gasparetto [UNESP] (My University, 2012)
Malabar spinach is a non-conventional vegetable propagated mainly by seeds. This research evaluated the propagation by stem cuttings as an alternative method of propagation and verified its effect on growth of the vegetable. Plantlets propagated by seeds and stem cuttings were grown in greenhouse and their growth were evaluated in five successive intervals of 21 days each, with the first evaluation carried out 60 days after the transplanting. The results showed that the propagation methods have influence on the Malabar spinach growth. Plants propagated by seeds display slow, but vigorous growth, with larger relative yield of leaves and tender leaves, while plants propagated by cuttings showed fast initial growth, with rapid fruit formation. Thus, the propagation by cuttings is more suitable for seed production, while propagation by seeds is more profitable for leaves production.
Growth and yield of Malabar spinach (Basella alba L.) in relation to the propagation method
Keywords: Cuttings; Non-conventional vegetable; Seeds